The Students’ Perspectives of Small Group Discussion for Enhancing Their Speaking Abilities - Zuhro, Cholimatus; Setia Budi, Agus (Journal of English in Academic and Professional Communication, 2024)
This study aimed to explore students' perspectives on small group discussions in the context of teaching and learning speaking skills. A descriptive qualitative research approach was employed, involving 26 participants enrolled in the Basic English course during their first semester in the Horticulture Plantation Study Program at Politeknik Negeri Jember. Data collection utilized questionnaires, specifically a Google Form poll with multiple-choice question types, and interview questions. The questionnaires and interviews sought to understand the participants' perceptions of the effectiveness of small group discussions in developing their speaking abilities. The findings of the study revealed positive aspects of students' perceptions regarding small group discussions and their impact on enhancing speaking skills. The majority of participants expressed that engaging in small group discussions significantly contributed to their speaking development. Moreover, the research identified a correlation between students who demonstrated a keen interest in refining their speaking abilities and the benefits derived from participating in small group conversations. The results underscored that student perceived small group discussions as instrumental in their speaking skill development, highlighting the motivational aspect of these interactions. Additionally, the lecturer played a pivotal role in aiding students in overcoming obstacles encountered during the learning process.